Impact of arthritis on the perceived need and use of mental healthcare among Canadians with mental disorders: nationally representative cross-sectional study. Issue 12 (10th December 2020) - Howren, Alyssa; Aviña-Zubieta, J Antonio; Da Costa, Deborah; Puyat, Joseph H; Xie, Hui; De Vera, Mary A
Abstract : Objective: To evaluate the association between having arthritis and the perceived need for mental healthcare and use of mental health support among individuals with mental disorders. Design: A cross-sectional analysis using data from Canadian Community Health Survey—Mental Health (2012). Setting: The survey was administered across Canada's 10 provinces using multistage cluster sampling. Participants: The study sample consisted of individuals reporting depression, anxiety or bipolar disorder. Study variables and analysis: The explanatory variable was self-reported doctor-diagnosed arthritis, and outcomes were perceived need for mental healthcare and use of mental health support. We computed overall and gender-stratified multivariable binomial logistic regression models adjusted for age, gender, race/ethnicity, income and geographical region. Results: Among 1774 individuals with a mental disorder in the study sample, 436 (20.4%) reported having arthritis. Arthritis was associated with increased odds of having a perceived need for mental healthcare (adjusted OR (aOR) 1.71, 95% CI 1.06 to 2.77). In the gender-stratified models, this association was increased among men (aOR 2.69, 95% CI 1.32 to 5.49) but not women (aOR 1.48, 95% CI 0.78 to 2.82). Evaluation of the association between arthritis and use of mental health support resulted in an aOR of 1.50 (95% CI 0.89 to 2.51). Individuals with arthritis tended to use medications and professional services as opposed to non-professional support. Conclusion: Comorbid arthritis among individuals with a mental disorder was associated with an increased perceived need for mental healthcare, especially in men, underscoring the importance of understanding the role of masculinity in health seeking. Assessing the mental health of patients with arthritis continues to be essential for clinical care.